The Impact of Dual Uncertainties in Import Country Policies and Market Environments on Chinese Electric Vehicle Exports - Qiu Zhao; Chenxi Tang (World Electric Vehicle Journal)
The export of electric vehicles (EVs) is crucial for addressing global environmental challenges and achieving sustainable development goals. However, Chinese EV enterprises encounter significant obstacles when entering international markets due to the complex and variable policy and market environments of importing countries. This study explores the combined effects of import country policies and market environments on exports by utilizing panel data from Chinese EV companies’ exports to multiple countries, employing an OLS panel data regression model. The research examines the impact of dual uncertainty in the “policy–market” environment of import countries on Chinese EV exports. The findings indicate that uncertainty in the policy environment of importing countries has a significant negative effect on Chinese EV exports, while uncertainty in the market environment does not exert a substantial impact. Notably, when policy and market uncertainties interact, this dual uncertainty significantly exacerbates the negative effects of market environment uncertainty on Chinese EV exports. These results highlight the importance for Chinese EV enterprises to closely monitor policy changes in importing countries and adopt effective strategies to mitigate the impacts of dual uncertainties in the “policy–market” environment. Furthermore, it is recommended that governments of importing countries consider the implications of their policies on international trade, particularly in the context of EVs, to promote the healthy development of the global EV market.